Medium-term observations of salt marsh morphodynamics - Jin, Chuang; Gong, Zheng; Shi, Lei; Zhao, Kun; Tinoco, Rafael O.; San Juan, Jorge E.; Geng, Liang; Coco, Giovanni (Frontiers in Marine Science, 2022)
Salt marshes play a key role in attenuating wave energy and promoting sedimentation necessary to potentially adapt to sea level rise. The changes in the soil surface elevation, as a result of spatially and temporally varied sedimentation pattern, affect the hydrodynamics, marsh edge extension and so the sedimentation rate. Little attention has yet been paid to the medium-term sedim\entation under the influence of marsh extension. To fill this gap, we performed a 6-year (from 2012 to 2018) field observation to obtain the soil surface elevation of the cross-shore tidal flats in the center Jiangsu Coast (China). The salt marsh edge is extracted from remote sensing images using NVDI technique, which allows us to quantify the seaward extension of salt marshes. Results highlight that soil surface elevation in the salt marsh region varies spatially and temporally as a function of marsh topography, inundation frequency and distance to the salt marsh edge. The sedimentation rate reduces linearly shoreward as a result of increasing soil surface elevation in the marsh region. At the transition of salt marshes and bare flats, the sedimentation rate follows a parabolic relationship with the increase in distance to the salt marsh edge but decreases linearly at the more landward sites. The maximum sedimentation rate is initially located around the mean high-water level and moves towards the edge of the salt marsh as a result of marsh extension and increasing soil surface elevation. Our field observations reveal these medium-term marsh dynamics and provide a unique dataset for development, testing and validation of numerical simulations to enhance predictions of the overall evolution of tidal flats.